Aspek Gramatikal dan Leksikal Pada Lirik Lagu â€œAku Cinta Allahâ€ Group Band Wali - Sari, Intan Purnama; Setyorini, Ririn (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
This research is to describe (1) how is the form of grammatical cohesion in the song lyrics of "Aku Cinta Allah" Band Guardian Group, and (2) how is the form of lexical cohesion in the song lyrics "Aku Cinta Allah" Wali Band Group. Hasi and discussion of finding the grammatical aspects found are references (References) with the words you found, pelipapan (Elipsis) with each word found, and conjunctions (concatenation) with found lexical words and aspects found are repetitions (Repetition) found by the word Who You Are, Me, Help and Every, and Synonym (Comparative Word) love, love, weakness, and helplessness.Keywords: song lyrics; lexical; grammatical.